Pengaruh User Generated Content (UGC) Pada Media Sosial Tiktok Terhadap Minat Beli Konsumen (Studi Pada Konsumen Produk Glad2glow di Kota Bandung) - Dewi, Natasya Anjelina; Tiorida, Ermina; Raharso, Sri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study was conducted to analyze User Generated Content of Glad2Glow products, purchase interest of Glad2Glow products, and the influence of User Generated Content on TikTok social media on purchase interest of Glad2Glow products in Bandung City. This study applies a quantitative approach with Purposive Sampling technique and involves 200 respondents from Glad2Glow product consumers in Bandung City. Data collection was carried out through the use of Google Form which has been validated and realizable with the help of SPSS software version 27.0. Data analysis techniques include data instrument tests, classical assumption tests, correlation tests, simple linear regression tests, T hypothesis tests (partial), and determination coefficient tests used to analyze the influence of User Generated Content on purchase interest. These findings indicate a positive and significant relationship between User Generated Content and purchase interest. This study only focuses on User Generated Content on TikTok social media on purchase interest of Glad2Glow product consumers in Bandung City. These findings are expected to provide better insight into the development of digital marketing and consumer behavior in the era of social media in shaping purchase interest among Glad2Glow product consumers in Bandung City.